Algorithm of management of patients with acute cholestatic hepatitis (Clinical case presentation) - T. A. Deyeva; Ye. N. German; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To show diagnostic and treatment algorithm for patients with cholestatic syndrome by the example of clinical case.Features of clinical case. The patient self treated for a long time by various infusions and medicinal herbs (including the Chinese tea; celandine) with no medical control. On a background of such treatment within several weeks symptoms of severe general weakness, jaundice of skin and scleras, pruritus, disorders (inversion) of sleep have appeared. Multiple elevation of serum transaminase level and markers of cholestasis was revealed. The acute cholestatic hepatitis was diagnosed, that developed on a background of herbal infusions and celandine intake. As a result of the carried out therapy (desintoxication preparations, ursodeoxycholic acid) and cancellation of all possible hepatotoxic agents symptoms of disease gradually regressed and improvement of laboratory parameters was marked.Conclusion. In the submitted case a main role in recognition of an etiology of liver disease have played by careful taking of past history and analysis of all possible causes of disease, that can be the key point in diagnostic search and choice of patient management tactics.